Sonic Hedgehog modulates EGFR dependent proliferation of neural stem cells during late mouse embryogenesis through EGFR transactivation - Palma, Veronica A.; Reinchisi, Gisela; Parada, Margarita; Oyanadel, Claudia; Shaughnessy, Ronan; Lois, Pablo; Gonzalez, Alfonso (Frontiers in Cellular Neuroscience, 2013)
Sonic Hedgehog (Shh/GLI) and EGFR signaling pathways modulate Neural Stem Cell (NSC) proliferation. How these signals cooperate is therefore critical for understanding normal brain development and function. Here we report a novel acute effect of Shh signaling on EGFR function. We show that during late neocortex development, Shh mediates the activation of the ERK1/2 signaling pathway in Radial Glial cells (RGC) through EGFR transactivation. This process is dependent on metalloprotease activity and accounts for almost 50% of the EGFR-dependent mitogenic response of late NSCs. Furthermore, in HeLa cancer cells, a well-known model for studying the EGFR receptor function, Shh also induces cell proliferation involving EGFR activation, as reflected by EGFR internalization and ERK1/2 phosphorylation. These findings may have important implications for understanding the mechanisms that regulate NSC proliferation during neurogenesis and may lead to novel approaches to the treatment of tumors.